KONTROL LAMPU DENGAN MENGGUNAKAN MODUL NODEMCUESP8266 V.3 BERBASIS TELEGRAM BOT - Muhammad Jimi Rizaldi; Erick Radwitya (Politeknik Negeri Ketapang, 2022)
Internet technology can connect two computers to communicate with each other, both sending and receiving data even at great distances. By using the Telegram Bot we can connect to the module used to control the lights. With this remote light control tool, we can turn off or turn on the lights with an unlimited distance as long as we are connected to the internet network. By using a smartphone we can do this under any circumstances and check the status of the lights that we control whether they are on or off. Control lights via Telegram using components in the form of lights, relays, NodeMCU ESP8266 modules. After programming the NodeMCU ESP8266 module, in the design of this tool the following components are obtained, namely 4 20 watt lamps, 1 4 channel relay, ESP8266 NodeMCU Module with a maximum input of 12 volts.